Interactions et transactions identitaires d'immigrés noirs dans l'espace public et les centres de santé au Maroc - Annélie Delescluse (L’Année du Maghreb)
Moroccan society is divided over the fate of migrants from Central and West Africa (known as sub-Saharans) for whom the Cherifian Kingdom is a medium or long-term country of residence. On the one hand, civil society mobilised on their behalf and a new migration policy was launched, propelling Morocco to the forefront of migration issues on the African continent and internationally. On the other hand, they experience socio-racial violence on the streets and in public facilities because of their precarious administrative, social and economic situation, and attitudes of rejection on the part of part of the Moroccan population. How do so-called sub-Saharan migrants discover that they are black in Morocco, and how do they deal with this reality? What form does xenophobia take in social relations, and what effects does it have on daily life and migration routes? How do migrants react to these realities, and how do they get round the depreciatory gestures? This article first looks at the vagaries of everyday life and the processes of racial otherness encountered in the street and on public transport. The article then looks at the thorny issue of medical interactions between Moroccan healthcare staff and sub-Saharan patients who claim to be victims of racism in healthcare. We will see that the domination felt by the latter towards medical staff, and towards the Moroccan population more generally, also triggers and sustains a set of tense behaviours and refusals that lead to perilous situations, particularly when they abandon the care prescribed in Morocco and return to their countries of origin. Finally, the article looks at three possible reactions to these processes of othering: victimisation, the reversal of stigma and racialisation in return. Through these reactions, we will see that African immigrants in Morocco demonstrate agentivity in coping with the various hazards of their daily lives, even if they incorporate the idea of race to which they are referred. The tactics they use enable them to carry out transactions or negotiations in order to deal with their identity, which is primarily the bearer of various stigmas. The article is based on an ethnographic study carried out mainly in Rabat between 2016 and 2020, during which I followed the daily and ordinary lives of around fifty men and women from West Africa (Côte d'Ivoire n= 28, Senegal n= 17) and Central Africa (Cameroon n=7 Democratic Republic of Congo and Congo, n=4), aged between 25 and 35. They arrived in Morocco between 2012 and 2014 (three quarters of them via the airports), and their profiles (sportsmen and women, pilgrims, traders, adventurers, etc.), motivations and administrative status were varied. At the time of the survey, they were working on the fringes of the salaried sector (building and civil engineering, car washing, domestic work, agricultural work, commerce, shoemaking) or in call centres in Rabat or Casablanca